Urban political strategies in times of crisis: A multiscalar perspective on smart cities in Italy. (October 2019) - Smigiel, Christian
European cities are experiencing a mushrooming of a new urban imagery amid multiple types of crisis. In fact, the 'smart city' has become a widely spread vision used by a variety of powerful key actors as well as a top-down urban political strategy that is applied in order to promote new arrangements, models and technologies for almost all policy areas. By using the Italian case as a point of reference, this paper analyses how smart city strategies are institutionalized and embedded in times of crisis on different spatial scales. Therefore, the paper adapts a strategic-relational approach that provides a conceptual framework for understanding the spatial dimension of smart city strategies. It argues that smart city strategies reflect a set of multiscalar political strategies leading to new responsibilities and powers on a local scale, as well as the creation of new state territoriality. Smart cities in Italy are part of metropolitan reforms that strengthen the role of large cities while reproducing existing territorial inequalities. Furthermore, they are used to create new public–private partnerships and new investment opportunities on different spatial scales. In addition, a content analysis of smart city rankings and reports sheds light on the modes of representation of smart city strategies, analysing them as elements of policymaking in times of crisis.